1986
DOI: 10.1113/jphysiol.1986.sp015969
|View full text |Cite
|
Sign up to set email alerts
|

Changes by acetylcholine of membrane currents in rabbit cardiac Purkinje fibres.

Abstract: SUMMARY1. The ionic mechanisms underlying the effects of acetylcholine (ACh) on electrophysiological properties of rabbit cardiac Purkinje fibres have been analysed using the two-micro-electrode voltage-clamp technique on short preparations.2. In normal Tyrode solution, ACh shifted the membrane currents in the outward direction at potentials positive to the K+ equilibrium potential, EK, and in the inward direction at potentials negative to EK. When ACh effects were studied in various [K+].the reversal potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…increased by ACh). In Carmeliet & Mubagwa (1986a), it was shown that ACh does not change the slow inward current in the absence of catecholamines. It is therefore unlikely that a steady component of the slow inward current accounts for the Cs+-insensitive ACh-induced component.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…increased by ACh). In Carmeliet & Mubagwa (1986a), it was shown that ACh does not change the slow inward current in the absence of catecholamines. It is therefore unlikely that a steady component of the slow inward current accounts for the Cs+-insensitive ACh-induced component.…”
Section: Resultsmentioning
confidence: 99%
“…Changes in time-dependent currents might also contribute to the effect of ACh. A decrease of the late outward current, ix (see Carmeliet & Mubagwa, 1986a), would tend to superimpose on the effect of ACh on other currents. This will result in a total ACh-induced current decreasing with time during depolarizations to potentials positive to -50 mV and in an inward tail on return to the holding potential.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In preparations pre-treated with catecholamines, ACh becomes able to decrease the amplitude of the slow inward current, isi (see Carmeliet & Mubagwa, 1986a), probably by antagonizing the stimulation produced by catecholamines on the adenylate cyclase system (Watanabe 243 E. CARMELIET AND K. MUBAGWA & Besch, 1975;Biegon & Pappano, 1980). The time course of the inhibitory effect of ACh on isj was investigated.…”
Section: Time Course Of Acetylcholine Effects On Membrane Currentsmentioning
confidence: 99%